A STUDY OF JAMBI BATIK ARTISANS IN INNOVATION AND STRATEGIC DECISION-MAKING TO INFLUENCE THE DEVELOPMENT AND RESILIENCE OF THE JAMBI BATIK INDUSTRY - Octavia, Ade; Heriberta, Heriberta; Sriayudha, Yayuk (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This study investigates Jambi batik artisans' resilience and innovative strategies in overcoming economic challenges and disruption in the textile industry. Using a qualitative approach with data analysis based on Miles and Huberman’s interactive model, the research delves into how these artisans creatively adapt to changing market demands by incorporating alternative materials, eco-friendly dyes, and distinctive local designs to enhance product appeal. The study also explores their marketing strategies, which leverage digital platforms and direct sales at exhibitions, significantly expanding their consumer reach and maintaining competitiveness. This combination of traditional artistry and modern tactics supports the preservation of Jambi's cultural heritage. It aligns with Sustainable Development Goals (SDGs) related to responsible production, decent work, and gender equality. The findings reveal that Jambi batik artisans successfully merge traditional motifs with contemporary styles, allowing them to preserve local identity while meeting evolving consumer preferences. Notably, this research highlights how artisans overcome resource limitations and market fluctuations by engaging in strategic collaborations, fostering community support, and adopting digital innovations to broaden their reach. This study's novelty lies in its focus on the dual role of cultural preservation and sustainable economic practices, offering insights into how traditional industries can thrive in modern contexts. The outcomes emphasize that with strategic innovation, the Jambi batik industry has substantial potential for sustainable growth, presenting a model for other cultural enterprises seeking resilience in the face of globalization and economic challenges.